Alberto Flores Galindo utopia, history, and revolution - Aguirre, Carlos 1958-; Walker, Charles F. 1959- (Brill, 2025)
"A renowned Peruvian historian, Alberto Flores Galindo (1949-1990) wrote fundamental books on Andean utopianism, José Carlos Mariátegui, subaltern Lima, and more. He participated in fiery debates on the left about Marxism, democracy, and socialism. Written by two specialists in Peruvian history, this book addresses many of his major topics and contributions, including Peru's rupture with Spanish colonialism, his role as a Marxist public intellectual, his relationship with the Cuban Revolution, the Shining Path and human rights, and his passion for literature. The book introduces English readers to the life and work of one of Latin America's major Marxist thinkers"--
Keywords: Flores Galindo, Alberto -- 1949-1990; Sozialismus; Politische Philosophie; Utopie; Peru; Flores Galindo, Alberto; Historians / Peru / Biography; Intellectuals / Peru / Biography; Social scientists / Peru / Biography; Utopian socialism / Peru / History / 20th century; Peru / Intellectual life / 20th century; Peru / Politics and government / 20th century; Lima (Peru) / Biography; Intellectuels / Pérou / Biographies; Spécialistes des sciences sociales / Pérou / Biographies; Pérou / Politique et gouvernement / 20e siècle; Biografie